Vaping-Associated Dermatitis and Reversible Airway Obstruction in a Non-Atopic Adult - Ocio, John Jay; Ong, Remedios (Philippine Journal of Allergy, Asthma and Immunology, 2025)
We present a case of a 42-year-old non-atopic male who developed pruritic rashes and reversible airway obstruction after initiating daily e-cigarette use. Symptoms included cutaneous eruptions and asthma-like respiratory complaints, with objective evidence of bronchial reversibility. This highlights vaping's potential to trigger systemic hypersensitivity and new-onset airway reactivity. Clinicians should consider vaping as a possible cause in patients with unexplained rashes and respiratory symptoms, even in the absence of prior atopy.